PRINSIP - PRINSIP GOOD GOVERNANCE DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PEKANBARU - dailiati, surya; hernimawati, hernimawati; sudaryanto, sudaryanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2017)
Public agencies that provide public services accountable, transparent, accessible, easily accessible information is a public instasi some traits that have applied the principles of good governance. Office of Population and Civil Registration Pekanbaru is the public agency that organizes public services in the field of population and civil registration, including the service of National Identity Card, Family Card, registration and issuance of birth certificates and death.This study aims to determine how the Principles of good governance. This research is a qualitative descriptive study. The sampling technique used was purposive sampling technique. Data collection technique used observation and interview and questionnaire. The data used in this study is the apparatus of the state and civil society is managing the administration. The data obtained were analyzed using descriptive analysis technique that consists of data reduction, data presentation and conclusion. Based on the research that the application of the principles of good governance is good but there are some that need to be improved. Namely, equality and the supremacy of law. For that we need an improvement in some aspects.